Diversity of Colletotrichum species on strawberry (Fragaria × ananassa) in Germany - ROSE, Christiane; DAMM, Ulrike (Phytopathologia Mediterranea, 2024)
Anthracnose caused by Colletotrichum species is an important disease of strawberries (Fragaria × ananassa), but the species causing this disease in Germany have not been investigated based on modern systematics. By using multi-locus phylogenetic analyses (ITS, act, gapdh, chs-1, his3, tub2), 58 Colletotrichum isolates from previous and recent collections, obtained mainly from fruit anthracnose of cultivated strawberries in Germany, were identified or re-identified as C. fioriniae, C. godetiae and C. nymphaeae (C. acutatum species complex) as well as C. anthrisci and C. lineola (C. dematium complex). Colletotrichum nymphaeae was dominant; most of the isolates belonged to one clonal lineage that occurs on strawberries throughout Europe, the United States of America, and some African and Asian countries. One of the other two haplotypes was distantly related and only represented by recently collected material. All other species, each of one haplotype, had only been isolated once or twice from German strawberries. This is the first report of C. anthrisci in Germany and for the genus Fragaria worldwide; all the other isolated fungi are newly reported for this genus in Germany. Comparisons of morphological characteristics of the species identified demonstrate that these features are of limited use for identification, even to species complex level. In pathogenicity tests, all five species caused anthracnose symptoms on ripe fruit of Fragaria × ananassa ‘Asia’.